Preparing Lawyers for the Twenty-First Century - William Twining (Legal Education Review, 1992)
We are already preparing lawyers for the twenty-first century. Whether we are doing so as efficiently, as imaginatively or as professionally as we might is another matter. Higher education of any kind tends to be an expensive enterprise which, even from a purely utilitarian point of view, can only be justified as a long-term investment. Those who are currently undergraduates or who are undergoing professional training or apprenticeship, or who are learning by experience as fledgling practitioners will only be able properly to evaluate their basic education and training after the year 2000. Accordingly today’s topic is concerned with the here and now. In the first part of this paper I shall draw attention to a number of recent trends and developments in legal education in the Commonwealth that give some grounds for optimism. In the second part I shall argue for a concerted effort to foster realistic and enlightened expectations about their legal education among law students and young lawyers. One hopes that a significant proportion of the current generation of law students and young lawyers will look back to the 1990s as a period of relative enlightenment in which some of the truisms of educators in the late twentieth century were transformed in a sustained way from pious aspirations into practical working principles. These truisms include the following: that education is a life-long enterprise; that most higher education should be self-education; that the main role of undergraduate education is learning how to learn; that standard distinctions between academic and practical, theory and practice, liberal and vocational are false dichotomies that are mischievous as well as misleading; and that any body of lawyers worth preserving must take seriously its claims to be a learned profession. These truisms are part of the standard aspirational discourse of Law Day addresses, after-dinner speeches, public lectures and Commonwealth Law Conferences. But those who control recruitment, vocational training, professional examinations, and related matters, by their practice and example as well as their talk often send quite different messages to law students and intending lawyers. These contradictory messages include the following: that studying law is mainly a matter of acquiring knowledge; that coverage is more important than depth; that what legal subjects one covers in primary legal education is more important than whether they are good vehicles for intellectual training; and that one is finished with academic study, critical analysis and even reading as soon as one graduates ... that “theory” is something one grows out of about the age of twenty-one. Such ideas are almost the exact opposite of the noble aspirations enumerated above. Just because they are more often assumed in practices and attitudes than in public statements they can have a more direct and subversive influence on the expectations and attitudes of law students and intending lawyers than pious sermons. One purpose of this paper is to make a plea to those responsible for vocational training, professional examinations and above all recruitment to take seriously the content of the messages they communicate to the young and, where appropriate, to consider changing their tune.